THE EFFECTS OF ENVIRONMENTAL PROTECTION AND SOCIAL SPENDING ON SOCIETAL WELL-BEING: PANEL EVIDENCE FROM SELECTED OECD COUNTRIES - BİLGİN, Ebru and YILDIRIM, Zerife (Economic Annals, 2025)
The increasing prominence of environmental protection reflects its integral role in shaping global economic and social agendas. As the consequences of human activity increasingly extend beyond financial implications to affect broader societal well-being, environmentally conscious policy design has become essential. In this regard, proactive environmental strategies are crucial not only for ecological sustainability but also for strengthening the overall quality of human capital. This study investigates the relationship between environmental protection efforts and human development through a panel data analysis of 15 OECD member states, from 2010 to 2021. The empirical findings reveal a longterm equilibrium relationship among the variables, with environmental protection expenditures contributing positively to improvements in the Human Development Index. Conversely, long-run coefficients for public expenditures on education and health appear to have a negative association with human development. Furthermore, causality tests indicate the presence of unidirectional causal links between the examined variables. Based on these results, the study offers policy insights that underscore the importance of effectively channelling resources toward environmental initiatives to support sustainable human development.